The inequality predicament - Brychtová, Šárka (Univerzita Pardubice, 2006)
The United Nations Report on the World Social Situation 2005: the Inequality Predicament, issued today, sounds the alarm over persistent and deepening inequality worlwide. The Report focuses on the chasm between the formal and informal economies, the widening gap between skilled and unskilled workers, the growing disparities in health, education and opportunities for social, economic and political participation.
Keywords: sociální nerovnosti; Chudoba; bída; globalizace; OSN; socioekonomická situace